2012
DOI: 10.4103/0255-0857.93039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the microscopic observational drug susceptibility assay for rapid and efficient diagnosis of multi-drug resistant tuberculosis

Abstract: MODS was found to be a sensitive and rapid alternative method for performing culture and DST to identify MDR-TB in resource poor settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…Our sensitivity of 100% and a specificity of 95.92% for MODS to detect MDR-TB are consistent with other reports (12,2124). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our sensitivity of 100% and a specificity of 95.92% for MODS to detect MDR-TB are consistent with other reports (12,2124). …”
Section: Discussionsupporting
confidence: 92%
“…in 2012 (21), who found a sensitivity of 94.12% and a specificity of 89.39% for MODS and to Zikum et al . in 2015 in China (22) whose also reported a sensitivity between 87.78% and 94.4% and a specificity between 96.8% and 100%, our data showed a good correlation between the MODS assay and a reference tuberculosis test.…”
Section: Discussionmentioning
confidence: 92%
“…However, labor costs are specific to the setting of the study, and the large variability of labor costs will impact the conclusions of cost effectiveness in different settings. Additionally, several studies have shown that the cost for micro broth culture is lower than those of other available culture methods [9], [10], [11] [16]. In the liquid broth assay, 3 positive cultures (1.5%) and 4 negative cultures (3.3%) were contaminated.…”
Section: Discussionmentioning
confidence: 99%
“…Global efforts for TB control, especially in resource limited settings, are being challenged by the lack of rapid, reliable and inexpensive techniques for the detection of M. tuberculosis [7], [8], [9], [10]. Results from the conventional culture detection methods come too late to influence a timely decision on patient management.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high cost, Middlebrook media are rarely used routinely in countries with limited resources. Thin layer agar (TLA) is a solid medium-based test, which, on a similar principle as the Microscopic Observation Drug Susceptibility assay (MODS) method (Lazarus et al, 2012 ), relies on the inoculation on a thin layer of Middlebrook 7H11 agar for the detection of cording M. tuberculosis microcolonies using an inverted microscope (Runyon, 1970 ). Later, incidental isolation of M. tuberculosis on blood agar (Drancourt and Raoult, 2007 ) suggested that this routine medium could support isolation of M. tuberculosis .…”
Section: Introductionmentioning
confidence: 99%